2012
DOI: 10.1002/jor.22263
|View full text |Cite
|
Sign up to set email alerts
|

Silencing the expression of connexin 43 decreases inflammation and joint destruction in experimental arthritis

Abstract: The objective of the present study was to determine whether the expression of connexin 43 (Cx43) effected on inflammatory conditions in rat fibroblast-like synoviocytes (FLS) and on rat model of rheumatoid arthritis (RA). The expression of Cx43 in rat FLS stimulated with lipopolysaccharide (LPS) was confirmed by real-time reverse transcriptase polymerase chain reaction (RT-PCR). The effects of small-interfering RNA targeting Cx43 (siCx43) on pro-inflammatory cytokines and chemokine were assessed by real-time R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 30 publications
1
46
0
Order By: Relevance
“…12 As such, Cx43 might be a target in which pharmacological agents can block the gap protein and slow or halt the progression of OA in the shoulder. A study by Tsuchida et al 51 showed in a rat model of rheumatoid arthritis that inhibition of Cx43 protected against the development of inflammation and joint destruction. Increased Cx43 in osteoarthritic joints has biological plausibility considering that increased mechanical load can lead to both the degradation of joints and an increase in Cx43.…”
Section: Discussionmentioning
confidence: 99%
“…12 As such, Cx43 might be a target in which pharmacological agents can block the gap protein and slow or halt the progression of OA in the shoulder. A study by Tsuchida et al 51 showed in a rat model of rheumatoid arthritis that inhibition of Cx43 protected against the development of inflammation and joint destruction. Increased Cx43 in osteoarthritic joints has biological plausibility considering that increased mechanical load can lead to both the degradation of joints and an increase in Cx43.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, immunofluorescence analysis of bones shows that most cells presented Panx3 at the growth plate [29], suggesting that OCs might express this protein. Finally, Cx43, forming either GJCs or HCs, is involved in the development of rheumatoid arthritis because silencing Cx43 in rat lower limbs reduces the number of OCs and delays the onset of this disease [174]. This suggests that Cx43 expression by OCs might contribute to the development of this disease and might be a relevant target for its treatment.…”
Section: Expression Of Cxs In Antigen-presenting Cellsmentioning
confidence: 99%
“…We also showed that the expression of Cx43 was enhanced in synovial tissue from rats with the collagen-induced arthritis (CIA) model of RA. 17 In this study, we demonstrated that the expression of Cx43 in RASFs was significantly enhanced by TNF-a stimulation and that high levels of Cx43 expression was associated with infiltration of inflammatory cells into synovial tissue of RA patients. These findings suggest that increased expression of Cx43 may be involved in the pathogenesis of RA synovitis.…”
Section: Discussionmentioning
confidence: 57%